APLIKASI PELAYANAN TERPADU KECAMATAN (PADUKA) DI KECAMATAN GUNUNGSITOLI UTARA KOTA GUNUNGSITOLI - Frans Harmonis Buluaro; Maria Magdalena Bate'e; Arman Mendrofa; Eliagus Telaumbanu (Lembaga Pengembangan Kinerja Dosen, 2026)
Public service is a crucial indicator in realizing good governance, particularly administrative services that directly interact with the community. The sub-district (kecamatan), as the frontline of local government administration, plays a strategic role in providing efficient, effective, and accountable correspondence and administrative services. This study aims to analyze the problems in administrative correspondence services at the Gunungsitoli Utara Sub-District Office and to examine the urgency of implementing a digital-based service system as a solution to improve the quality of public services. This research employs a descriptive qualitative approach through preliminary observations of administrative service processes. The findings reveal that correspondence services are still conducted manually with lengthy procedures, heavy reliance on physical documents and photocopies, conventional archival systems, and dependence on the physical presence of authorized officials, which collectively result in low efficiency and effectiveness of service delivery. Furthermore, the absence of a digital service system limits transparency and accessibility, particularly for communities living in geographically remote areas. The implementation of the PADUKA (Integrated Sub-District Service) application is considered a viable solution to streamline service procedures, enhance service speed, transparency, and accountability. However, the success of service digitalization requires adequate human resources, technological infrastructure, and improved digital literacy among the community. Therefore, the transformation toward digital-based administrative services in Gunungsitoli Utara Sub-District is a strategic step to enhance public trust and ensure sustainable improvement in public service quality.